When Good Intentions Are Not Enough: Ethical Tensions in Rare Disease Care in Indonesia - Pramudani, Ardita; Eryani, Ika; Utari, Agustini; Winarni, Tri (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
This case study examines a child with a rare genetic condition in Indonesia whose access to care depended on community mobilization in the context of limited institutional support, revealing a tension between the principles of beneficence and justice in resource-constrained health systems. While acts of beneficence are morally commendable, we argue that justice should take priority by motivating equitable, institutional solutions that avoid reliance on ad hoc community goodwill and prevent unequal access to care among patients with comparable needs.